KNOWLEDGE MANAGEMENT - WARIER SUDHIR (VIKAS PUB. NEW DELHI, 2008)
This book discusses the strategies, techniques and tools to facilitate the design and development of an organizational knowledge management system.
Keywords: MANAGEMENT KNOWLEDGE (F-21)